What to Consider When Creating Digital-based Learning Materials for Creative Writing Class - WINDA CANDRA HANTARI (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
This study aims to identify preferred aspects in creating digital-based learning materials for Creative Writing students in the COVID-19 pandemic situation. The lack of direct interaction with the lecturer and actual classroom causes them to be less enthusiastic about learning. Thus, a suitable composition of digital media is needed to solve the respective students' problems. Interactive, flexible, helpful, and easy to access are the key points of the composition. It may provide audio and video that help students to enhance their comprehension. The researchers use a descriptive qualitative approach regarding students' preferences to expose the actual data. The result shows that 89,7% of students prefer asynchronous, interactive, and flexible digital video available online as it allows them to get the virtual presence of the teacher and go through the material repeatedly. This particular media must be equipped with a microblogging platform for discussion, such as WhatsApp Group. The video-based media also provides a solution since internet connection has always been an obstacle for students holding classes with synchronized video conferencing.